LINGUISTIK DAKWAH: ANALISIS BAHASA FORMAL DAN INFORMAL DALAM PENYEBARAN ISLAM DI ERA DIGITAL - Hopid Jidan; Nabila Khairunnisa; Nabila Yusuf; Radita Dian Eka Mauldya; Edi Suresman (Cahaya Ilmu Bangsa Institute, 2025)
The development of Islamic da'wah in the digital era brings changes in the way religious messages are conveyed, especially in language selection. The use of formal and informal language in digital da'wah can affect the extent to which audiences understand Islamic teachings. This study aims to examine how the choice of language in digital da'wah affects the understanding of da'wah recipients. Using a quantitative approach and survey method, this study involved 124 respondents who actively access digital da'wah. The results show that the majority of respondents prefer and more easily understand da'wah delivered in casual and communicative language compared to formal language. A more familiar language is more effective in delivering religious messages in the digital space. These results provide insight for Islamic preachers and communicators in designing digital da'wah strategies that are more effective and easily understood by the audience.